Supply chain practices and performance: the indirect effects of supply chain integration. Issue 6 (1st August 2016) - Kaliani Sundram, Veera Pandiyan; Chandran, VGR; Awais Bhatti, Muhammad
Abstract : Purpose: – The purpose of this paper is to employ a newly developed framework to examine the complex relationship between different components of supply chain practices, supply chain integration (SCI) and supply chain performance (SCP) in the Malaysian electronics sector. Design/methodology/approach: – This study utilizes survey data of 156 electronics firms in Malaysia and tested the research framework and hypotheses. In addition to the traditional approach of Barron and Kenny (1986), the Sobel test as well as a bootstrapping approach, which is deemed for small sample size, is used to formally test the indirect effects of SCI in the model. Findings: – SCI has fully and partially mediated the relationship between supply chain management practices (SCMPs) and SCP. SCI fully mediates the relationship between SCP and three of the SCMPs, namely, information quality, agreed vision and goals and postponement strategies. The relationship of supply strategic partnership, customer relation management, information sharing with SCP were partially mediated by SCI. Risk and reward sharing is found to be non-significant. These insights allow managers to effectively utilize the different components of SCMPs for SCI and performance. Practical implications: – For supply chain practitioners, the results of the study can be useful in integrating SCMPs and SCI on improving SCP. Practitioners should take into account the mediating effect of SCI in designing their supply chain management approach to production. Originality/value: – To the authors' best knowledge, this paper is one of the first to address the mediating effect of SCI between SCMPs and overall performance of the supply chain.